Assessment of molecular markers associated with resistance or susceptibility to Fusarium wilt TR4 in Musa acuminata ssp. malaccensis / Fatimah binti Kayat - Kayat, Fatimah (2009)
Bananaandplantain(Musaspp.)arestaplefoodcropsintropicaland subtropicalcountriesandalsoplayakeyroleintheeconomicofmanydeveloping countries.However,thetenyearreview(1996-2005)oftheproductionofthecrop showedthatthelandusageforbananaandplantainhadincreasedbuttheyieldhadbeen reducedduringthesameperiod.InMalaysia,PanamadiseaseorFusariumwiltcaused byFusariumoxysporumf.sp.cubenseVCG01213/16alsoknownasTropicalrace4 (TR4)isthemajorandthemostdestructivediseasewhichcausesconsiderablelossto theMalaysianbananaexporttrade.Conventionalbananabreedingforresistanceto Fusariumwiltishamperedbysterility,triploidy,longgenerationtimeandthelackof appropriatetestingsites.Biotechnologicaladvancesinvolvinginvitropropagation, somaticembryogenesisandmolecularmarkersprovidetoolsforgeneticrelationship studiesandQTLanalysisthuscouldenhancethedevelopmentofcultivarsadaptedto changingenvironments. Theuseofgenesfromthewildcroprelativeshavebeenrecognizedinbreeding programsofmanycrops.Inthisstudy,thestrategyapproachistodevelopnew populationswithtraitsspecifictothepathogenfromtheindigenouswildbananaMusa acuminatassp.malaccensis(AA)whichhasbeenshowntohaveveryhighresistanceto FOCTR4.Maturedseedswereextractedfromfruitbunchesoffourrandomopencross populationsofwildbananainordertoproduceseedprogeniesraisedthroughzygotic embryoculture.Embryogerminationwasachievedwithoutanyseedtreatmentinthe darkfortwoweeksbeforebeingplacedunderlight.Individualseedprogenieswere subjectedtoseveralin-vitrostagesinordertogainuniformplantletswithreplicatesfor diseasescreening.DifferentdegreesofresponsetoFusariumoxysporumf.sp.cubense TR4wereobservedinwildbananaseedprogeniesaswellastheirF1hybridpopulations whichprovidedapotentiallyusefulgeneticresourceforthedevelopmentofdisease resistancemarkersthatcouldbeexploitedinamarker-assistedselection. AhighdegreeofpolymorphisminwildbananaseedprogeniesshownbyRAPD m arkersprovidedgoodearlyevidenceforthepotentialusefulnessofpolymorphismandse gregationstudiesusingmolecularmarkers.AnalysisofRAPD,STMSandAFLPm arkersinthisstudydidnotshowanycleardifferentiationbetweenresistantandsus ceptibleindividuals.However,markersgeneratedbythosemethodswereincludedinl inkagemapdevelopment.Atotalof18markershadbeengeneratedfromRAPDa nalysiswhile14SSRmarkerswereobservedfromSTMSanalysis.Atotalof4657ba ndswasgeneratedfrom30EcoR1+3xMseI+3,oneEcoR1+3xMseI+2and43P stI+2xMseI+3primercombinations.The639markersconsistingof607AFLPs,14S SRsand17RAPDsmarkersweredeterminedontwomappingpopulations(resistancea ndsusceptibilitytoFOCTR4).Atotalof471markers(286Pst-markers,155Eco-m arkers,17RAPDmarkersand13STMSmarkers)wereanalyzedforthesusceptiblem appingpopulationwhile414markers(249Pst-markers,143Eco-markers,9RAPDm arkersand13STMSmarkers)wereanalyzedfortheresistantmappingpopulation.L inkageanalysisofthedataresultedinthegenerationoftwosetsoflinkagemapsc onsistingof32linkagegroupsfortheresistantmappingpopulationand37linkageg roupsforthesusceptiblemappingpopulation.Themapshaveprovidedthebasisoff uturemappingandmarker-assistedbreedingstudiesandstrategiesforthisbanana.